Development of a real-time automated family classification system - Chen, George Fengrong. (2011)
The local binary pattern LBP, which was originally used for texture analysis, is now being proposed for improvement by the addition of threshold information. The LBP is superior in computational simplicity and this allows this project to be implemented in real time family classification system. As such, this project has two main components, one is to access the performance of proposed LBP with thresholds information which is in the back end stage, and the other is to implement this in real time application which is in the front end stage.